2009
DOI: 10.1002/app.30056
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical reinforcement of poly(1‐butene) using polypropylene‐grafted multiwalled carbon nanotubes

Abstract: The mechanical properties of poly(1-butene) reinforced by pristine multiwalled carbon nanotubes (MWNTs) and polypropylene-grafted MWNTs (PPg-MWNTs) were evaluated. The incorporation of pristine MWNTs to PB led to an improvement in stiffness, but not in strength, ductility, and toughness. In comparison, PP-gMWNTs were able to improve the stiffness, strength, and toughness of PB significantly, without compromising the ductility. The mechanical properties of PB improved with increasing amount of PP-g-MWNTs up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Layered silicates, which are usually preferentially distributed in the amorphous phase within spherulites [40][41][42], were shown to partly mimic this entropic effect by locally increasing the pressure on the nascent crystalline domains [7]. It was observed that large montmorillonite aggregates were desirable in delivering this effect, because small tactoids are too flexible and they are not able to exert pressure on the macromolecular chains [43][44][45]. This is confirmed by our results.…”
Section: Discussionsupporting
confidence: 78%
“…Layered silicates, which are usually preferentially distributed in the amorphous phase within spherulites [40][41][42], were shown to partly mimic this entropic effect by locally increasing the pressure on the nascent crystalline domains [7]. It was observed that large montmorillonite aggregates were desirable in delivering this effect, because small tactoids are too flexible and they are not able to exert pressure on the macromolecular chains [43][44][45]. This is confirmed by our results.…”
Section: Discussionsupporting
confidence: 78%
“…For instance, the presence of 1.5% CNT in PE will lead to a 40% drop in the fracture toughness of PE. 22 McNally et al showed that the addition of pristine MWNTs to PE matrix caused a significant decrease in fracture toughness. The reason of this effect is related to the weak interfacial interaction between PE and CNT.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Polymer nanocomposites made with small amounts of monofunctional polymer chains grafted to the nanotubes have been shown to greatly improve the mechanical properties of the composite, [5][6][7] and are more effective than ungrafted pristine nanotubes in this regard. [8] The grafting of polymer chains to nanotubes can be achieved by functionalizing the nanotube in order to introduce reactive groups onto the surface, followed by reaction with a polymer chain possessing a complementary reactive end group. Using a difunctional reactive polymer allows for the possibility of the chain to be grafted at both ends, forming a ''loop''.…”
Section: Introductionmentioning
confidence: 99%